The church as a catalyst for transformation in the society - Akanbi, Solomon O. (HTS teologiese studies, 2017)
This article evaluates the activities of the church, especially the Pentecostal Movement in Nigeria, and their contribution to national development. It identifies the social, economic and political problems in Nigeria and discusses their interconnections and impacts on the development in Nigeria. It also identifies and analyses the approaches of the African Pentecostal Movement to socio-economic and political problems and evaluates the impact of these responses to the Nigerian society. Finally, it explores the role of the African Pentecostal churches in nation building and the transformation of the people of the south-western part of Nigeria. The church as a religious and social organisation, driven by moral and social principles as contained in the fundamental teachings and doctrine of Christian faith, is expected to play an important role towards the social change and the improvement on society’s value system. This will lead to the transformation of the social life and put society in a holistic growth- and development-oriented direction. This article investigates and evaluates the assumption that Christianity is capable of influencing the society positively, using the Pentecostal movement as a case study. The article looks at the Pentecostals’ contribution to social, political and economic lives of the people of the Nigerian society, especially the south-western part of Nigeria since the inception of the Pentecostal Movement in Nigeria. This article argues that Pentecostalism as a movement is fast growing and gaining attention from both Christians and non-Christians and has a major role to play in transforming the socio-political and economic lives of the people of south-western Nigeria. As such, this article offers a critique of the Pentecostal Movement using the Redeemed Christian Church of God, Deeper Life Bible Church and Living Faith Church as case studies.